Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Perkimtan Kota Palembang Dengan Lingkungan Kerja Sebagai Variabel Intervening - Muhammad Hendri Mulyadi; Djatmiko Noviantoro; Yusro Hakimah (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This study aims to test and prove the effect of compensation and work environment on the performance of employees of the Palembang City Perkimtan Service, both directly and indirectly, with work motivation as an intervening variable. The population in this study were all employees of the Palembang City Perkimtan Service, totaling 82 people. The sampling technique used the saturated sample method, so that the entire population was used as a research sample. Thus, the number of samples used was 82 employees. The data were analyzed using the Structural Equation Model (SEM) method operated through the Partial Least Square (PLS) program. The results of the study indicate that compensation variables affect work motivation, work environment variables affect work motivation, compensation variables affect performance, work environment variables affect performance, and work motivation variables affect performance. In addition, compensation variables also affect performance with work motivation as an intervening variable, and work environment variables affect performance with work motivation as an intervening variable.